2021
DOI: 10.1186/s40902-021-00303-9
|View full text |Cite
|
Sign up to set email alerts
|

Salivary exosomal microRNAs as biomarkers for head and neck cancer detection—a literature review

Abstract: Background MicroRNAs (miRs) are small, non-coding mRNA molecules which regulate cellular processes in tumorigenesis. miRs were discovered in extracellular environment and biological fluids, carrying marks of head and neck squamous cell carcinoma (HNSCC). They were also identified in abundance in salivary exosomes, in which they are protected by exosome lipid barrier against enzymatic injuries and therefore, the accuracy of exosomal miR-based cancer detection increase. This systematic review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Notably, the expression of miRNA-34 was greater in high-grade OSCCs, and the expression of miRNA-486-5p assisted the detection of stage I OSCC, demonstrating the potential usefulness of salivary exosomal miRNAs for the early diagnosis of cancer [10]. In the same way, it has been found that miRNAs-4484 and 10b-5p are biomarkers of the malignant transformation of oral lichen planus and oral dysplasia in OSCC [8,10,11], and a lower expression of miRNA-200a has been associated with a higher risk of malignant transformation and oral cancer. Finally, miR-365 has been found to regulate transcription, promoting oncogenesis and metastasis in some cancers but suppressing these processes in others [12].…”
Section: Exosomal Mirnas With Diagnostic Capacitymentioning
confidence: 79%
See 2 more Smart Citations
“…Notably, the expression of miRNA-34 was greater in high-grade OSCCs, and the expression of miRNA-486-5p assisted the detection of stage I OSCC, demonstrating the potential usefulness of salivary exosomal miRNAs for the early diagnosis of cancer [10]. In the same way, it has been found that miRNAs-4484 and 10b-5p are biomarkers of the malignant transformation of oral lichen planus and oral dysplasia in OSCC [8,10,11], and a lower expression of miRNA-200a has been associated with a higher risk of malignant transformation and oral cancer. Finally, miR-365 has been found to regulate transcription, promoting oncogenesis and metastasis in some cancers but suppressing these processes in others [12].…”
Section: Exosomal Mirnas With Diagnostic Capacitymentioning
confidence: 79%
“…In this way, miRNAs with oncogenic function are upregulated and responsible for silencing tumor-suppressor genes that can modulate the onset, development, and metastasis of cancer cells. Conversely, miRNAs with tumor-suppressor function are downregulated, reducing the modulation of oncogenes and maintaining malignity [8].…”
Section: Salivary Microrna (Mirna) In Oscc Diagnosis and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Various other metabolites and biomarkers have been shown to concentrate within EXOs and show additional promise in the identification and monitoring of HNC. Within the blood and saliva of HNSCC patients, microRNAs (miRNA)—or small, non-coding mRNA molecules—have been noted to mediate various cellular processes in tumorigenesis [ 121 ]. Various investigators have demonstrated the role of miRNA and salivary-derived EXOs as novel HNSCC biomarkers [ 122 , 123 , 124 , 125 ].…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…The ROC curves obtained, which showed obvious discrimination between normal and cancer patients (AUC = 0.864 and 0.960 for miR-196a and miR-196b, respectively) suggested that these miRNAs are specific circulating miRNA biomarkers for oral cancer patients when compared with the healthy controls. Otherwise, exosomal miRNAs can be identified in the TME and can circulate freely in body fluids, which also makes them suitable for acting as non-invasive biomarkers in clinical applications [116][117][118]. Utilizing a new generation of miRNA sequencing technology, Langevin et al demonstrated that exosomal miR-486-5p, miR-486-3p, and miR-10b-5p were detectable in saliva for a set of HNSCC patients, and these might be exploited as noninvasive salivary biomarkers [119].…”
Section: Clinical Implications Of Mirna In Hnsccmentioning
confidence: 99%